Contracts Induced by Means of Bribery: Should they be Void or Valid? - Mathias Nell (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2008)
This paper argues that contracts induced by means of bribery should be valid. Nullity and voidability decrease the incentive for voluntary disclosure, assist corrupt actors with enforcing their bribe agreements and provide leeway for abuse. Thus, they run counter to effective anti-corruption. It is argued that other instruments are more suitable for preventing corruption.
Keywords: G34; G38; K12; K14; K42; 330; Bribery; Contracts; Corruption; Due Diligence; Enforcement; Impugnment; Liability; Leniency; Nullity; Private Law Validity; Voidability; Voluntary Disclosure (Program)